PROGRAM ESD DI JEPANG : KAJIAN PENERAPAN PROYEK ESD DI SMA DI PREFEKTUR AICHI - Murni Ramli (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The research aims to analyse the ESD Project in Japanese School, particularly its practices in ASP-net Schools in Aichi Prefecture Japan, one of the modernized area in central Japan. Research had been conducted from June to July 2013. Data had been collecting through interview to the staff of the Teacher Training Centre (TTC) of Aichi, Biology Teachers of Zuiryo High School, and ESD Project Leader of Toyota Higashi High School. Document and literature analysis was conducted to obtain the information on country policies. The findings are, Japanese schools had already practiced an ESD-like program called Shogoutekina gakushuujikan or Integrated Study Course (ISC), three years prior the UN-based ESD Program had been adopted by the government. ISC was introduced to Japanese schools curriculum since 2000, and had been widely implemented in all level of education. The practices of ESD varied among the schools, but it is always related to the local environment, society issues, and international understanding.  This paper will explain ESD practices at Toyota Higashi High School. The Toyota Higashi High Schools had been adopted UNESCO ASP-net School in 2012, in which the ESD practices have to be based on UNESCO-based ESD Project. The ESD program has been integrated to the recent curriculum, which are mostly implemented in shogotekina gakushuu jikan.  Students from grade 1 to grade 3 learn about locality, environment education, and international understanding. Materials for ESD program was developed by teachers and it fixed the UNESCO system.  They also cooperate with Teacher Training Center of Aichi to formulate the local based-ESD substances. Keywords : ESD Project, Integrated Study Course, Shogotekina Gakushuu Jikan, environmental education